The Elaborated Environmental Stress Hypothesis as a Framework for Understanding the Association Between Motor Skills and Internalizing Problems: A Mini-Review - Mancini, Vincent O.; Rigoli, Daniela; Cairney, John; Roberts, Lynne D.; Piek, Jan P. (Frontiers in Psychology, 2016)
Poor motor skills have been shown to be associated with a range of psychosocial issues, including internalizing problems (anxiety and depression). While well-documented empirically, our understanding of why this relationship occurs remains theoretically underdeveloped. The Elaborated Environmental Stress Hypothesis by Cairney, Rigoli, and Piek (2013) provides a promising framework that seeks to explain the association between motor skills and internalizing problems, specifically in children with Developmental Coordination Disorder (DCD). The framework posits that poor motor skills predispose the development of internalizing problems via interactions with intermediary environmental stressors. At the time the model was proposed, limited direct evidence was available to support or refute the framework. Several studies and developments related to the framework have since been published. This mini-review seeks to provide an up-to-date overview of recent developments related to the Elaborated Environmental Stress Hypothesis. We briefly discuss the past research that led to its development, before moving to studies that have investigated the framework since it was proposed. While originally developed within the context of DCD in childhood, recent developments have found support for the model in community samples. Through the reviewed literature, this article provides support for the Elaborated Environmental Stress Hypothesis as a promising theoretical framework that explains the psychosocial correlates across the broader spectrum of motor ability. This evidence promotes the external validity of the framework for use across the broader spectrum of motor ability. However, given its recent conceptualisation, ongoing evaluation of the Elaborated Environmental Stress Hypothesis is recommended.